Analisis Fungsi Media Instagram bagi Promosi Felize Beauty Bar - Lioni Lioni; Wulan Purnama Sari (Kiwari, 2022)
Instagram is a social media that is widely used by people of various ages with various interesting features that can make users continue to be loyal to Instagram users and make Instagram a promotional medium. With Instagram's features, it helps business people to do promotions easily, cheaply, and practically through Instagram social media. The purpose of this study was to determine the function of Instagram media in promoting products or services. The theory used in this study is the theory of new media, Instagram, Instagram features, and Instagram as a promotional media. The research uses a descriptive qualitative approach with case study research methods, data collection is done by interview, observation, documentation, and literature study. The results show that the Instagram feature is useful when promoting on Instagram media, especially in interactions between followers and business accounts that offer services or products, the type of interaction that gets the most attention on the Instagram reels feature and Instagram stories.Instagram merupakan media sosial yang banyak digunakan oleh masyarakat dari berbagai kalangan usia dengan berbagai fitur menarik yang mampu membuat pengguna terus setia menjadi pengguna dan menjadikannya media promosi. Kini, fitur-fitur Instagram dapat membantu pebisnis untuk melakukan promosi dengan mudah, murah, dan praktis. Tujuan penelitian ini adalah untuk mengetahui fungsi media Instagram dalam mempromosikan produk atau jasa. Teori yang digunakan dalam penelitian ini adalah teori media baru, Instagram, fitur Instagram, dan Instagram sebagai media promosi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode penelitian studi kasus. Pengumpulan data dilakukan dengan wawancara, observasi, dokumentasi, dan studi kepustakaan. Hasil penelitian menunjukkan bahwa fitur Instagram berguna saat melakuka promosi di media Instagram, terutama dalam interaksi antara pengikut dengan akun bisnis yang menawarkan jasa atau produk. Diketahui, jenis interaksi yang paling mendapat perhatian pada fitur reels Instagram dan story Instagram.